Nematicidal effect of plant extracts from Quassia amara and Brugmansia suaveolens against Meloidogyne sp. on tomato plants in Nicaragua. - Salazar-Antón, Wilber (2014)
The nematicidal activity of leaves of Quassia amara L. (Simaroubaceae) and flowers of Brugmansia suaveolens L. (Solanaceae) was evaluated against Meloidogyne sp. during a study conducted at the Agricultural Campus of the National Agricultural University in León (UNAN- León). The plant material was dehydrated, ground and the compounds quassin and scopolamine were extracted using methanol as a solvent. Then a study was conducted in vitro to evaluate mortality in second stage juveniles of Meloidogyne sp. after exposure to extracts (12, 24 and 48 hours). Subsequently, extracts were also evaluated in tomato plants established in pots under greenhouse conditions, and the corresponding nematode population was quantified after exposure to the extract (25, 50 and 75 days of exposure to extract, DEE). In vitro tests with extracts of B. suaveolens and Q. amara diluted at 10% showed that the highest rate of nematode mortality occurs after 48 h of exposure, leaving 89% and 78% of all juveniles dead, respectively. In the test in pots, several aspects were evaluated including juvenile mortality, the plant galling index (GI), and the nematode reproduction factor (RF). The best result for Q. amara was obtained at 25 DEE, with 80% of mortality, a GI of 1 (in a scale from 0-5) and a RF of 0.2. Similarly, the best effect for B. suaveolens, was obtained at 25 DEE with a 71% of mortality, a GI of 1.2, and a RF of 0.29. These results from tests in vitro and in pots results indicate that both extracts have nematicidal activities, as they significantly reduced the nematode population (P≤ 0.05), the reproductive ability and the incidence of root galling in tomato plants.